A clinical audit of thoracotomy done in a tertiary care center - Ahmad, Zeeshanuddin; Agrawal, Deepak; Desai, Sanjay M.; Jain, Amar (International Journal of Research in Medical Sciences, 2018)
Background: Sri Aurobindo Medical College and Post Graduate Institute is a tertiary care center in Indore. The surgical oncology department is performing various oncological surgeries. One subspeciality is thoracic surgery, where surgeries for benign as well as malignant cases are being done. Thoracotomy is done for various lung, pleural and mediastinal pathology. Open and VATS are two main modalities with each having their pros and cons. Methods: All thoracotomies done from 2016 to January 2018 were included in the study. Decortications, wide local excision, lobectomies, pneumonectomies, hilar lymph node dissections were done. Results: Total 30 cases were done in a span of 2 years. Of these 9 cases were done for a malignant origin, 4 for benign tumor, 3 for benign non-infective disease and rest 14 for infective origin. Posterolateral thoracotomies were done most often. Average duration of the procedure was 157 minutes. Average blood loss was approximately 340 ml. Mean duration of stay was 10.9 days. Conclusions: Thoracic oncologic procedures are less often done due to paucity of the cases. However, surgical oncologist being well versed with the anatomy, relations and oncologic concepts can perform both neoplastic as well as infected cases. With increasing number of cases, the standard of care is increasing, operating time is lessened, complications are brought down, and the results are better.